(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Background Malaria is a life-threatening disease caused by parasites that are transmitted to peoplethrough the bites of infected female Anopheles mosquitoes in numerous endemic areas of India. It ispreventable and curable. In 2019, there were an estimated 229 million cases of malaria worldwide.Material and method 100 samples were included in the study, which further processed for QBC, rapidcard (antigen detection test) and peripheral blood smear diagnostic test for diagnosis of malaria.Result and observation Out of total 100 cases thick smear detected 73 positives compared to 70 by thinsmear, 72 by dipstick and 69 by QBC. Thick smear proved to be better than the other methods. Whiledipstick closely followed thick smear, thin smear and QBC had a back stage in comparison.Conclusion Thick smear proved to be better than the thin smear methods. QBC (quantitative Buffy coat)and thick smear had the disadvantage of difficulty in species identification